2002
DOI: 10.1128/jvi.76.2.895-904.2002
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Engineered Vesicular Stomatitis Virus in Gene Therapy: Application for Treatment of Malignant Disease

Abstract: We report here the generation of recombinant vesicular stomatitis virus (VSV) able to produce the suicide gene product thymidine kinase (TK) or cytokine interleukin 4 (IL-4). In vitro cells infected with the engineered viruses expressed remarkably high levels of biologically active TK or IL-4 and showed no defects in replication compared to the wild-type virus. Recombinant viruses retained their ability to induce potent apoptosis in a variety of cancer cells, while normal cells were evidently more resistant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
220
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(231 citation statements)
references
References 26 publications
(35 reference statements)
6
220
0
3
Order By: Relevance
“…24,25 Recombinant VSVs expressing the herpes simplex virus thymidine kinase or the cytosine deaminase suicide genes have been reported by Barber's group. 32,33 Their results suggest that the use of the prodrug-suicide gene strategy may add synergy to the effectiveness of oncolytic VSV in cancer treatment. An alternative strategy of cytotoxic gene therapy was recently introduced by Bateman et al, 34 demonstrating that plasmid-mediated expression of viral fusogenic membrane glycoprotein efficiently killed tumor cells through induction of fusion to form large multinucleated syncytia.…”
Section: Mutant Vsv For Treatment Of Breast Cancer O Ebert Et Almentioning
confidence: 99%
“…24,25 Recombinant VSVs expressing the herpes simplex virus thymidine kinase or the cytosine deaminase suicide genes have been reported by Barber's group. 32,33 Their results suggest that the use of the prodrug-suicide gene strategy may add synergy to the effectiveness of oncolytic VSV in cancer treatment. An alternative strategy of cytotoxic gene therapy was recently introduced by Bateman et al, 34 demonstrating that plasmid-mediated expression of viral fusogenic membrane glycoprotein efficiently killed tumor cells through induction of fusion to form large multinucleated syncytia.…”
Section: Mutant Vsv For Treatment Of Breast Cancer O Ebert Et Almentioning
confidence: 99%
“…The mechanism of VSV oncolysis also involves the induction of apoptosis by as yet undetermined mechanisms, though predominantly utilizes the caspase-9 pathway (Balachandran et al, 2000b). Studies by a number of groups have now shown robust proapoptotic oncolytic ability against tumors in athymic nude mice as well as in syngeneic tumors in immunocompetent animals (Balachandran and Barber, 2000;Balachandran et al, 2001;Fernandez et al, 2002;Obuchi et al, 2003;Stojdl et al, 2003;Ebert et al, 2004). VSV has also been shown capable of exerting its antitumor effects against metastatic breast adenocarcinoma when inoculated at sites distant from the tumor and when introduced intravenously (Balachandran and Barber, 2000;Balachandran et al, 2001).…”
Section: Vsv As a Cancer Therapeutic Agentmentioning
confidence: 99%
“…For instance, VSV harboring a mutant M is defective in the ability to suppress host antiviral responses including the IFN response, compared to wild-type viruses (Stojdl et al, 2003). A major advantage of using VSV as an oncolytic agent includes that this virus is genetically malleable and large gene inserts/ genes can be placed inside the genome for heterologous expression (Schnell et al, 1996;Fernandez et al, 2002;Porosnicu et al, 2003). The ability to modify VSV through genetic engineering, obviously affords the prospect of creating new generations of custom-made VSV vectors that contain immunomodulatory and/or suicide cassettes designed to increase their antitumor activity.…”
Section: Vsv As a Cancer Therapeutic Agentmentioning
confidence: 99%
“…Recombinant VSV carrying the Herpes virus TK enzyme has been shown to phosphorylate the non-toxic prodrug ganciclovir, facilitating its DNA integration and subsequent local toxicity. 13,15 A similar strategy was employed with VSV expressing the human sodium iodine symporter that resulted in the accumulation of radioactive iodine at the tumor site. 16 Both of these recombinant VSV strategies were shown to delay tumor growth in murine models; however, their action is restricted to cells that are directly infected by VSV.…”
Section: Introductionmentioning
confidence: 99%